It's All in Your Mind - Cox, Noel (Estados Unidos | ESTADOS UNIDOS ‎ Page Publishing, Estados Unidos, 2004)
It's All in Your Mind" is a story about a guy born of poor parents, just before the Great Depression. He never made a big salary, never went to a formal college, never received a pension and never received unemployment, food stamps or any other form of assistance. Yet he lived like a king, At least he always thought so. That guy was me and this is my story
Sin Especificar
Keywords: Mente-Guías | Circunstancia-Control | Mente-Poder